The Spread Of The Australian Redclaw Crayfish (Cherax quadricarinatus von Martens, 1868) in Malaysia - Awangku Shahrir, Naqiuddin; Khairul Adha, A.Rahim; Shabdin, Mohd Long; Faznur Fateh, Bte Firdaus@Nicholas (Penerbit UMT, 2016)
The introduction of alien crayfish species has resulted in changes of native species communities throughout the world. The Australian redclaw crayfish Cherax quadricarinatus were introduced in Malaysia for aquarium and aquaculture industry since 1980s. The current paper presents the distribution of the species in Malaysia through sampling trips, market surveys and focused interviews. Multiple size specimen in populations obtained from Sungai Benut (Johor) and Suai (Sarawak) confirms the establishment of the species in both west (Malaysian Peninsular) and east Malaysia (Borneo). There are no reports yet of any native species displacement or other ecological impacts in Malaysia caused by the redclaw introduction, although the potential cannot be dismissed totally. The growing redclaw culture industry could facilitate the spread of C. quadricarinatus faster and further in the near future.